Coeliac disease. Issue 1 (January 2016) - Anderson, Cheryl; Berrill, James
Coeliac disease is an autoimmune condition where there is damage to the small intestine triggered by exposure to dietary gluten. Gluten is the collective name for proteins contained in wheat, barley and rye. This article aims to inform readers on the current guidance on when and how to investigate patients for possible coeliac disease, and how to manage patients with the condition.